Urbanismo social inclusivo como mecanismo de enfrentamento da criminalidade: reminiscências da Escola de Chicago, o modelo Medellín e as intervenções urbanísticas da Operação Cidade Segura em São Luís. - COSTA, Mauricio José Fraga (2019)
The present research aims to demonstrate how practices of inclusive social urbanism can help to reduce crime rates. Some aspects of the theoretical contribution built by the Sociological School of Chicago, to prove its validity in the example inaugurated for Medellín, that through an integrated policy of implementation of public works of very high quality managed to reduce the alarming rates of crime in that city. Medellín, through inclusive social urbanism, managed to promote a substantial improvement in the quality of life of the citizens and thus reduce the criminogenic indices. With regard to São Luís, some urban interventions promoted by Operation Cidade Segura will be analyzed to verify its effectiveness as a tool to fight against crime.